Los costos de producción y su impacto en la rentabilidad de la empresa de Diseño Deportivo Kapital de la parroquia Veintimilla, cantón Guaranda, provincia Bolívar, año 2017 - Rochina Chileno, Luis Enrique (2018)
This research work is focused on the cost system in order of production and its impact on the profitability of the company, with the aim of contributing to the improvement of the production process of the KAPITAL Company of the city of Guaranda province of Bolívar, dedicated company to the manufacture of sportswear. Thus, the proposed proposal was developed taking into account the theoretical parameters related to the cost system by production orders and the research methodology applied in the present investigation was the qualitative modality, in the same way the types, methods, and methods were used. research techniques and instruments, gathering information necessary for the development of the proposal. In the evaluation of the objectives the deductive and analytical method was used, which allowed to evaluate the problems found in the company, which we have extracted based on their financial statements, and the information collected from the same source. Besides being of great importance the completion of research work where they meet the objectives set out in the project, the results obtained in this research will help in the proper management and operation of accounting operations and their owner take timely and accurate decisions since. The present investigation is focused on the theoretical framework with its philosophical and legal foundation. The analysis and interpretation of the results obtained by means of the technique and collection instrument such as surveys and interviews were also carrie. The main objective of this research work is the realization of a proposal that allows to determine the real production costs of the company of sports clothing for a better production and profitability of the Kapital company and evaluate the management of this, for this purpose research methods and techniques were used, as well as taking into account the 2016 financial statements such as: State of economic situation and the statement of financial position, applying an analysis by means of the application of the financial indicators for the determination of its management and financial. For all the above, it is considered important and necessary to control the raw material, labor and indirect costs, through a technical system that allows the appropriate allocation of the aforementioned elements, which is why in the present work is offers a theoretical and practical presentation of cost accounting. Finally, the conclusions and recommendations that are the main part of the work are exposed, as this way the owner can count on a timely accounting information related to the production of his company.